Grain Quality Engineering for Organic Metal Halide Perovskites Using Mixed Antisolvent Spraying Treatment. Issue 1 (19th November 2019) - Lee, Da Seul; Bing, Jueming; Kim, Jincheol; Green, Martin A.; Huang, Shujuan; Ho-Baillie, Anita W. Y.
Abstract : Herein, a mixed anti‐solvent treatment by spraying acetonitrile (ACN)‐added chlorobenzene (CBZ) for the fabrication of high‐quality perovskite films is proposed. While the lower‐boiling‐point ACN preserves the morphology of the perovskite film, it has a significant impact on perovskite crystallization dynamics. While CBZ is responsible for facilitating nucleation, ACN performs two functions. ACN as a weak polarity solvent allows the organic salt in the perovskite complex to be redissolved for perovskite formation and loosens the dimethyl sulfoxide (DMSO)–PbI2 bond for more rapid perovskite crystallization. For the mixed anti‐solvent treatment to be successful, an appropriate amount of ACN is the key and the use of spraying to dispense the mixed anti‐solvent is crucial. This is due to the more instant and rapid reaction caused by the ACN which is faster than spreading the ACN across the substrate by the spinning motion. The resultant film using an appropriate mixed anti‐solvent treatment is a pinhole‐free high‐quality perovskite film with larger grain and enhanced crystallinity compared with CBZ‐only treatment film. The best solar cell using this mixed anti‐solvent treatment with 20% of ACN and 80% of CBZ achieves a PCE of 20.1% due to the reduced recombination. Abstract : A mixed antisolvent treatment by spraying acetonitrile (ACN)‐added chlorobenzene (CBZ) for the fabrication of high‐quality perovskite films is reported. It is found that while the lower‐boiling‐point ACN preserves the morphology of the perovskite film, it has a significant impact on perovskite crystallization dynamics. Moreover, the method developed herein is scalable for future large‐area devices.